Ethics and the FDA. - Fielder, J. (IEEE Engineering in medicine and biology magazine)
This paper discusses the role of ethics in the Food and Drug Administration's approval process. The fundamental reasons for having a regulatory agency for food and medical products are ethical: concern for the safety and welfare of consumers. These basic ethical principles require a substantial number of regulations, guidances, procedures, and policies. If consumers of medical products are to be protected, every step of the process by which medical products are developed, tested, and marketed must be regulated